Urban Green Infrastructure for Poverty Alleviation: Evidence Synthesis and Conceptual Considerations - Shackleton, Charlie M. (Frontiers in Sustainable Cities, 2021)
The multiple benefits of urban green infrastructure (UGI) that support sustainable cities are increasingly acknowledged, and yet the bulk of research over the past decade or so has focused on only a small subset of the numerous benefits, notably recreation, physical and mental health, and regulating services. In contrast, there is very little information on the contribution of UGI to several of the other Sustainable Development Goals (SDGs), and in particular SDG 1 of reducing poverty, despite the pervasiveness of poverty globally. This paper considers the diverse direct and indirect ways in which UGI can contribute to poverty alleviation, drawing on the limited evidence from various regions of the world. The direct links between UGI and poverty alleviation is via three means, namely provision of (1) consumptive or provisioning goods such as wild foods and firewood, (2) employment in UGI development, maintenance, and restoration, and (3) land for urban agriculture, income generation and dwelling. There are also a number of indirect links such as cash savings, improved physical and mental health, improved social networks, improved educational outcomes, and regulation of potential natural disasters. However, the commonly unequal distribution of UGI within and between cities means that the poverty alleviation potential and benefits are inequitably distributed, often against those who are most in need of them, i.e., the urban poor. This demands greater attention to promoting the equitable distribution and quality of UGI and mainstreaming of UGI into poverty reduction strategies and programmes and vice versa, as well as greater examination of the links between UGI and poverty alleviation in a greater range of contexts.